2009
DOI: 10.1080/00048670903107609
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Treatment on Weight Gain and Metabolic Abnormalities in Patients with First-Episode Psychosis

Abstract: There were significant increases in BMI, serum levels of triglyceride, low-density lipoprotein and total cholesterol from baseline to 6 months. Mean increase in weight was 6.2+/-7.0 kg (p < 0.05) and 65% of the patients had clinically significant weight gain (i.e. > or =7% increase from baseline). On logistic regression lower baseline BMI, female gender, and younger age, were associated with clinically significant weight gain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…However, 7% weight gain is a marker for clinically significant weight change. 14,16–18 Additionally, we were unable to include in our analysis some key known correlates of weight gain, such as diet, exercise, and social support status. 62,63 We may also have sample selection bias; people who did not report their weight and thus were excluded from the study (n=50) may differ in important ways from those who reported their weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, 7% weight gain is a marker for clinically significant weight change. 14,16–18 Additionally, we were unable to include in our analysis some key known correlates of weight gain, such as diet, exercise, and social support status. 62,63 We may also have sample selection bias; people who did not report their weight and thus were excluded from the study (n=50) may differ in important ways from those who reported their weight.…”
Section: Discussionmentioning
confidence: 99%
“…14, 16 – 18 Definitions of clinically significant weight change are not consistent in the literature. Weight changes of any, 7 3%, 27 and 5% have also been used, 12, 13, 28 but we chose the more conservative measure of a 7% gain.…”
Section: Methodsmentioning
confidence: 99%
“…In the majority of cases, females have been found to have a higher prevalence of AAPD-induced weight gain (Aichhorn et al 2007;Haack et al 2009;Hakko et al 2006;Verma et al 2009). However, exceptions exist, where men have increased weight gain (Basson et al 2001) or no gender bias has been apparent (Lee et al 2004).…”
Section: Introductionmentioning
confidence: 97%
“…Inclusion criteria determined the selection of records which contained a diagnosis of schizophrenia (295.0, 295.10, 295.30, 295.90), schizoaffective disorder (295.70), delusional disorder (297.1) and psychotic disorder (298.90), [24] n = 214. Exclusion criteria included all cases with a secondary diagnosis of development or intellectual disability, those with a diagnosis of dementia or records that had missing biometric or lab data, leaving, n = 89.…”
Section: Methodsmentioning
confidence: 99%